Theory and Method in Higher Education Research. - Huisman, Jeroen (Emerald Group Publishing Limited, 2016)
This volume of Theory and Method in Higher Education Research contains contemporary contributions to international debates regarding the application and development of theory and methodology in researching higher education.
Higher Education Research Topics in Swedish Doctoral Theses and Changes Over Time.
Keywords: Education, Higher -- Research.; Education, Higher -- Research -- Methodology.; elektronické knihy; electronic books